Mainstreaming the Development of School Culture As A Reinforcement Of Character Values: A Literature Review - Nursaptini; Arif Widodo (Institute of Computer Science (IOCS), 2023)
Character building in the educational process is the main aspect that must be done before building intelligence. Students are expected to master etiquette before learning about science. Armed with the character of students, they will be wiser in practicing the knowledge they have in the future. There are various ways to internalize character values ??in students, one of which is through school culture. The role of school culture is very large in shaping the character values ??of students. Therefore, the mainstreaming of school culture development in strengthening character values ??needs to be investigated. In this study, it will be described how mainstream school culture is a reinforcement of student character values. The purpose of this study is to find out how the strategies that schools can do in mainstream school culture as reinforcement of character values. The research was conducted using the library method. Sources of data in this study are the results of previous studies that have been published in scientific journals, seminars, and books. Various sources of data that have been collected are then analyzed to find answers to the research objectives. The results of the literature study found that mainstreaming school culture development can be done in various ways, including forming good habits, and exemplary and strengthening character